1996
DOI: 10.1590/s1516-31801996000300002
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal ultrasonography assessment of ovarian volumes in postmenopausal women

Abstract: The authors evaluated ovarian volumes by transvaginal ultrasonography at different periods after menopause. Ninety-eight postmenopausal women with an average age of 51.9 years and a one-to eight-year postmenopausal period were studied. The control group consisted of 40 women during menacme with an average age of 31.8 years, who were also submitted to transvaginal ultrasonography to evaluate ovarian volume. There was no significant difference between right and left ovarian volumes in the study groups. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
(5 reference statements)
1
9
0
1
Order By: Relevance
“…Results for ovarian volume as measured by transvaginal ultrasound in postmenopausal women in vivo vary between studies from a mean/median of 1.1 mL to 2.5 mL2, 10, 18–22. The differences are probably to be explained by differences in age and number of years past menopause, because ovarian volume as measured by transvaginal ultrasound decreases with both19–21.…”
Section: Discussionmentioning
confidence: 95%
“…Results for ovarian volume as measured by transvaginal ultrasound in postmenopausal women in vivo vary between studies from a mean/median of 1.1 mL to 2.5 mL2, 10, 18–22. The differences are probably to be explained by differences in age and number of years past menopause, because ovarian volume as measured by transvaginal ultrasound decreases with both19–21.…”
Section: Discussionmentioning
confidence: 95%
“…23 In another study, in which data from 13,963 of the women enrolled in the University of Kentucky Ovarian Cancer Screening Project were analyzed to determine the relationship between ovarian volume and patient age, body height, and body weight, 24 the mean ovarian mass was similar to other reported values. 14,28 Although the upper limit of the normal range for ovarian volume in postmenopausal women is 10 ml, ovarian volume decreases with each decade of life between ages 30 years and 70 years. Therefore, using nomograms of ovarian volumes that are related to menopausal age may be more logical than applying a standard range of ovarian volume to all postmenopausal women.…”
Section: Sonographic Methods For Early Detection Of Ovarian Cancermentioning
confidence: 99%
“…Several authors have demonstrated a gradual reduction, with increasing age, in mean ovarian mass. 14,[27][28][29] In an analysis that excluded women receiving hormone replacement therapy, Tepper et al 27 noted a gradual decline in mean ovarian volume during the postmenopausal years, from 8.6 ± 2.3 ml in the first postmenopausal year to 2.2 ± 1.4 ml in the 15th year (Figure 1 had been receiving tamoxifen for breast carcinoma for at least 6 months and who were examined using transvaginal sonography. The control group comprised 311 postmenopausal women from the study by Tepper et al, 27 in which tamoxifen had not been given.…”
Section: Sonographic Methods For Early Detection Of Ovarian Cancermentioning
confidence: 99%
“…O ovário pós-menopáusico, em decorrência de sua exaustão folicular, é menor que seu equivalente na menacme (Nicosia, 1986;Wehba et al, 1996). Essa diminuição volumétrica -de aproximadamente 30% -é mais evidente no córtex ovariano, como conseqüência da acentuada diminuição de folículos em crescimento e maturação.…”
Section: Os Androgênios Na Pós-menopausaunclassified